Pattern recognition receptors in the development of nonalcoholic fatty liver disease and progression to hepatocellular carcinoma: An emerging therapeutic strategy - Huang, Chen; Zhou, Youlian; Cheng, Jiemin; Guo, Xue; Shou, Diwen; Quan, Ying; Chen, Hanqing; Chen, Huiting; Zhou, Yongjian (Frontiers in Endocrinology, 2023)
Nonalcoholic fatty liver disease (NAFLD) is characterized by excessive lipid accumulation and has become the leading chronic liver disease worldwide. NAFLD is viewed as the hepatic manifestation of metabolic syndrome, ranging from simple steatosis and nonalcoholic steatohepatitis (NASH) to advanced fibrosis, eventually leading to cirrhosis and hepatocellular carcinoma (HCC). The pathogenesis of NAFLD progression is still not clear. Pattern recognition receptor (PRR)-mediated innate immune responses play a critical role in the initiation of NAFLD and the progression of NAFLD-related HCC. Toll-like receptors (TLRs) and the cyclic GMP-AMP (cGAMP) synthase (cGAS) are the two major PRRs in hepatocytes and resident innate immune cells in the liver. Increasing evidence indicates that the overactivation of TLRs and the cGAS signaling pathways may contribute to the development of liver disorders, including NAFLD progression. However, induction of PRRs is critical for the release of type I interferons (IFN-I) and the maturation of dendritic cells (DCs), which prime systemic antitumor immunity in HCC therapy. In this review, we will summarize the emerging evidence regarding the molecular mechanisms of TLRs and cGAS in the development of NAFLD and HCC. The dysfunction of PRR-mediated innate immune response is a critical determinant of NAFLD pathology; targeting and selectively inhibiting TLRs and cGAS signaling provides therapeutic potential for treating NALF-associated diseases in humans.